A mixed-integer programming model of registration signalling and paging in a mobile communication network. (27th April 2021) - Khazaelpour, Payam; Sobhani, Ahmad; Roshani, Afshan
Handling traffic delays in a mobile communication network (MCN) is a principal problem due to time and cost expenses. Delays limit mobile coverage. Therefore, optimisation techniques and tools are applied to minimise delays. However, there is still a high chance that at some points the network will lose its integral connectivity and delays happen. Delays prohibit call transmissions and produce several breaks. System breaks/delays cause call pending for a connection. Accordingly, network partitioning happens, thus leads to disconnection. This paper proposes a mixed-integer programming (MIP) to minimise network delays while a reliable trade-off between registration signalling (RS) and paging (P) coverage distances is maintained. The proposed MIP is NP-hard. For this reason, a metaheuristic approach, genetic algorithm (GA), is developed and compared with it. MIP validation is endorsed by GA approximations in different random trials and comparative analysis investigates GA performance metrics in a numerical example.